Perencanaan Sarana dan Prasarana dalam Meningkatkan Kualitas Pembelajaran di MA Ponpes Qodratullah Langkan - Amilda, Amilda; Ibrahim, Ibrahim; Eliya, Leli (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to understand the process of planning facilities and infrastructure to improve the quality of learning at MA Ponpes Qodratullah Langkan-Banyuasin. This type of research is qualitative with a descriptive approach. Data collection methods include interviews, observations, and documentation. Data analysis techniques involve data reduction, data presentation, and verification as well as decision making. To ensure data validity, triangulation is used, including time, method, and source triangulation. Based on data analysis, it was found that the planning of facilities and infrastructure to improve the quality of learning at Madrasah Aliyah Pondok Pesantren Qodratullah Langkan is carried out through several stages. First, setting planning goals. These goals are established with the involvement of all parties, including the Head of the Madrasah, Deputy Head of the Madrasah for Facilities and Infrastructure, all teachers, and educational staff, aligning with the vision, mission, and objectives of the madrasah to ensure consistency with the institution's overall goals. Second, formulating the plan. Meetings involving all school stakeholders are held to formulate the plan, where all ideas and inputs are gathered and led by the head of the madrasah. Next, identifying the plan. This stage involves identifying missing facilities and necessary equipment for the learning process.